Analysis of CI, HI, and DVH Values for the Heart Organ with IMRT Technique for Post-Mastectomy Breast Cancer Patients - Jerry Djohan; Naura Shafila; Saleha Saleha; Sri Dewi Astuty; Ajeng Anggreny Ibrahim; Ayu Hardianti Pratiwi; Syamsir Dewang (Buletin Fisika)
Breast cancer has a high incidence rate in Indonesia, necessitating treatment to improve patient survival. One of the treatment methods used is radiotherapy with the Intensity Modulated Radiation Therapy (IMRT) technique, aimed at delivering an optimal radiation dose to the tumor while minimizing radiation exposure to healthy organs, such as the heart. This study aims to analyze the dose distribution in the organ at risk (OAR) of the heart and evaluate the conformity of the Homogeneity Index (HI) and Conformity Index (CI) values in post-mastectomy breast cancer patients undergoing IMRT.The research was conducted using data from 10 post-mastectomy patients at Pelamonia Hospital. Data were collected through Dose Volume Histogram (DVH) analysis, including radiation doses at 98%, 50%, and 2% of the target volume. Additionally, the volume exposed to a 95% isodose and the percentage of heart volume receiving a dose of 25 Gy were analyzed. This data was used to calculate HI, CI, and the total dose received by the heart.The results showed that HI values ranged from 0.14 to 0.45, indicating variability in dose uniformity. Most patients had CI values above 0.9, ranging from 0.87 to 0.96, indicating good dose conformity with the tumor volume target. The heart doses received by all patients were below the tolerance limits set by QUANTEC (V25<10%). The IMRT technique effectively minimizes radiation doses to the heart while providing a dose distribution that meets ICRU standards, with HI and CI values approaching optimal levels. These findings suggest that IMRT is an effective method for treating post-mastectomy breast cancer.